PENGARUH KUALITAS PELAYANAN, PERSEPSI HARGA DAN STRATEGI PEMASARAN TERHADAP KEPUASAN PELANGGAN PADA MIE GACOAN KARAWANG - Rizky Maulana; Marheni Eka Saputri (JURNAL LENTERA BISNIS, 2024)
Mie Gacoan is one of the trademarks of spicy noodles in Indonesia. Mie Gacoan itself is a subsidiary of PT Pesta Pora Abadi which is engaged in food and beverage. Its rapid development has made Gacoan Noodles now have branches almost throughout Indonesia, even now Gacoan Noodles is able to claim itself as the market leader in the ranks of spicy noodles in Indonesia. This study used quantitative methods with descriptive and causal research types. Respondents used consisted of customers who consumed Gacoan Noodles, with a total of 385 respondents using the sampling method. Data analysis was carried out by multiple linear regression analysis. The results of this study are marketing strategy variables, service quality and price perceptions have an effect on customer satisfaction of Mie Gacoan Karawang. The variables of service quality, price perception and marketing strategy partially and significantly affect the satisfaction of Gacoan Noodle Karawang customers with a coefficient of determination of 73.3%.